Climatologia dos casos de frentes frias fortes que atuaram em Cuiabá no período de 1996 a 2015 - Carmo, Edson Luis Ismael do (2022)
This work sought, from the study of climatology, understand and characterize the strong cold fronts that acted in the city of Cuiabá (MT) in the period 1996 to 2015. The choice for this study area stems from the fact that the capital of Mato Grosso is considered one of the hottest cities in the country, which aroused the interest to understand how the frontal systems passages occur in the region of Cuiabá, checking how the cold fronts interfered with the main atmospheric characteristics that occurred in the period under study, especially those called strong. The results indicated that the displacement of cold fronts that reached the region of Cuiabá, in the 20-year period studied, showed a displacement from the southwest to the northeast, with an elongation of the frontal branch toward the continent, whose formation occurred, on average, three days earlier in the region of Argentina. It was concluded that, in the southern region of Mato Grosso, there were greater incursions of cold fronts in the dry season (period from April to September). These cold fronts that reached Cuiabá carried a colder and drier air mass, which consequently made rainy episodes impossible, because one of the indispensable ingredients for the occurrence of precipitation was missing: humidity.